PMMA doped Multi Walled Carbon Nanotube (MWCNTs) microfiber for alcohol sensing application / Husna Abdul Rahman … [et al.] - Abdul Rahman, Husna; M. Haron, Haliza; Mat Isa, Naimah; Saad, Hasnida (Universiti Teknologi Mara Cawangan Pulau Pinang, 2019)
PMMA polymer microfiber doped Multi Walled Carbon Nanotubes (MWCNTs) was reported for alcohol sensing application. The sensitivity of the sensor is increasing relatively with the increment of the alcohol concentration which affects the transmission output power. However, the challenges are on choosing the right material and the simplicity on the fabrication of microfiber sensor for an improvement of the sensitivity of the sensor. A PMMA polymer microfiber doped MWCNTs was introduced for an application of alcohol detection system. Direct drawing technique was used to form a uniform waist size of microfiber sensor with 6μm diameter and 5mm length respectively. The performance of the fabricated sensor was tested with two types of alcohol, namely ethanol and 2-propanol at concentrations varying from 2% to 8% with 2% intervals. The performance which includes sensitivity, linearity and resolution were studied and analysed for the undoped PMMA and PMMA doped MWCNTs-doped polymer microfiber. The PMMA doped MWCNTs sensor which exhibited higher sensitivity for ethanol sensing with 83.23dBm/% with a linearity of 99.96% and a sensitivity of 73.75dBm/% with linearity 99.82% for 2-propanol sensing. The resolution has improved significantly by 0.0004% and 0.0007% respectively. In conclusion, PMMA doped MWCNTs was able to increase the sensitivity as well as the reproducibility of the microfiber sensor for the alcohol detection system.